Resilience and its relationship with disability in persons with bipolar disorder and schizophrenia: A comparative study - Arnab Datta; Dhrubajyoti Chetia (Indian Journal of Psychiatry)
Background: Resilience is the capacity to bounce back from adversity. Severe mental illnesses are associated with poor and heterogeneous functional outcomes. Symptom remission is inadequate to achieve patient-oriented outcome, and positive psychopathology constructs like resilience have emerged as possible mediators. An exploration of resilience and its association with functional outcomes can drive therapeutic endeavors. Aim: To assess and compare the influence of resilience on disability among patients diagnosed and treated for bipolar disorder and schizophrenia in a tertiary care facility. Methods: Study design – Hospital-based, cross-sectional, comparative design; study population – patients of bipolar disorder and schizophrenia with 2–5 years illness and Clinical Global Impression – Severity (CGI-S) <4; sampling procedure – consecutive sampling; sample size – 30 patients each; scales used – Connor–Davidson Resilience Scale (CD-RISC), Indian Disability Evaluation and Assessment Scale (IDEAS), and CGI-S; patients were evaluated with IDEAS, and 15 persons with and without a significant disability were recruited in each group of schizophrenia and bipolar disorder. Results: The mean CD-RISC 25 score for persons with schizophrenia was 73.60 ± 13.87, whereas that for persons with bipolar disorder was 78.10 ± 15.26. For schizophrenia, only CDRISC-25 scores are statistically significant (t = −2.582, P = 0.018) for predicting IDEAS global disability. For bipolar disorder, CDRISC-25 scores (t = −2.977, P = 0.008) and CGI-severity scores (t = 3.135, P = 0.005) are statistically significant for predicting IDEAS global disability. Conclusion: When disability is factored in, resilience is comparable in persons with schizophrenia and bipolar disorder. Resilience independently predicts disability in both groups. However, the type of disorder does not significantly affect the relationship between resilience and disability. Irrespective of diagnosis, higher resilience is associated with lower disability.